International auditing standards and their role in achieving financial transparency requirements in insurance companies - Nadhim, Ahmed Raad (Journal of Research in Social Science and Humanities, 2023)
The research discusses the role of International Auditing Standard No. 20, in achieving financial transparency, which has become an international requirement for organizations to classified and adopt their data as an economic indicator of the efficiency of the markets in which these organizations operate. And the research discussed the concept of international auditing standards and their relationship to achieving Elements of financial transparency through the application of its principles in organizations. And research reached a number of results, the most important is the weak interest of the auditing bodies in insurance companies to share the results of audit work with the media and the parties interested in the results of their work and their weak role in attracting researchers’ attention to the results of their work as part of the requirements Audit Standard No. 20.